2017
DOI: 10.1016/j.jep.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic- and antidepressant-like effects of an aqueous extract of Tanacetum parthenium L. Schultz-Bip (Asteraceae) in mice

Abstract: Anxiolytic- and antidepressant-like T. parthenium effects result, at least part from the involvement of the GABAergic system. Our results support the use of Tanacetum parthenium in traditional medicine and suggest its therapeutic potential in the comorbid anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…Moreover, it was displayed that having flavonoids including apigenin, the T. parthenium plant can interact with the benzodiazepine receptors including the GABA receptors and increase its activities. 13 In addition, in another study, the benzodiazepinic GABA activity of apigenin from the T. parthenium plant has been shown. 14 With the studies done in the field of active chemical compounds present in the TP, it has been identified that similar to the characteristics of T. parthenium, in this plant, abundant amount of flavonoids including apigenin and luteolin are found.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, it was displayed that having flavonoids including apigenin, the T. parthenium plant can interact with the benzodiazepine receptors including the GABA receptors and increase its activities. 13 In addition, in another study, the benzodiazepinic GABA activity of apigenin from the T. parthenium plant has been shown. 14 With the studies done in the field of active chemical compounds present in the TP, it has been identified that similar to the characteristics of T. parthenium, in this plant, abundant amount of flavonoids including apigenin and luteolin are found.…”
Section: Discussionmentioning
confidence: 93%
“…However, against this backdrop and in accordance with the findings of the present study, in the most recent study on T. parthenium , it was found that T. parthenium has anti‐anxiety and anti‐depression effects on the rats. Moreover, it was displayed that having flavonoids including apigenin, the T. parthenium plant can interact with the benzodiazepine receptors including the GABA receptors and increase its activities . In addition, in another study, the benzodiazepinic GABA activity of apigenin from the T. parthenium plant has been shown .…”
Section: Discussionmentioning
confidence: 94%
“…the number of head dippings and stretches number were also measure. In this model, a decrease in the percentage of time spent on the open arms and an increase in the percentage of time spent on the closed arms with respect to the control group are both associated with low anxiety levels [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effect seems to be mediated by the serotonergic system [350] and is blocked by HT 2A receptor antagonists and serotonin synthesis inhibitors but not by βand α 2 -noradrenergic receptor antagonists, indicating that the extract modulates the release/reuptake of serotonin [351]. Tanacetum parthenium has exhibited anxiolytic and antidepressant-like effects in various tests, prompting the authors to propose the involvement of the GABAergic system [352]. Terminalia bellirica exerted its antidepressant-like effects (FST and TST) in mice through interaction with the adrenergic (α 1 ), dopaminergic (D 2 ), and serotonergic (release/reuptake of 5-HT) systems [353].…”
Section: Dosementioning
confidence: 99%